Formação de docentes que atuam na Educação Superior (Revista de Educação Pública, 2012)
Este texto analisa a formação de docentes que atuam na educação superior, com base em três questões: espaço ocupado pelo tema na pauta de discussões dos problemas educacionais; instâncias responsáveis por tal formação; desafios postos aos programas de pós-graduação, no que se refere à temática. Buscou-se estabelecer relações com o cenário educacional mato-grossense, considerando dados do censo da educação superior publicados pelo MEC/ INEP. As análises indicam que, em Mato Grosso, há demanda por formação de docentes da educação superior, sobretudo no setor privado. Indicam também que a dimensão pedagógica dessa formação carece de mais atenção.Teacher training for those who act in Higher EducationAbstractThis text analyses the teacher training of those who act in Higher Education. The analysis was developed based on three issues: space occupied but the theme when educational problems are in discussion; elements responsible for such training; challenges to the postgraduation program referring to this thematic. An effort was made to establish relationships with the mato-grossense educational scenery, taking into consideration data from the census of higher education published by MEC/INEP. The results indicate that in Mato Grosso, there is a demand for the training of university teachers, mainly in the private area. They also show that the pedagogical dimension of this teacher training needs more attention.Keywords: Higher Education. Teacher training. Pedagogical dimension.